Comparison of the Effect of Er,Cr:YSGG Laser and Halita Mouthwash on Oral Malodor in Patients With Chronic Periodontitis: A Randomized Clinical Trial: Effect of Er,Cr:YSGG laser and Halita mouthwash on oral malodor - Poormoradi, Banafsheh; Gholami, Leila; Fekrazad, Reza; Hooshyarfard, Amirarsalan; Noorani, Ali Reza; Lotf Haghpanah, Zahra; Farhadian, Maryam (Journal of Lasers in Medical Sciences, 2021)
Introduction: Periodontal disease and tongue coatings are among the major factors associated with oral malodor. The present study, comparatively evaluated the effects of the Er,Cr:YSGG laser and Halita mouthwash as adjunctive treatments to nonsurgical periodontal debridement on oral malodor reduction in chronic periodontitis patients. Methods: Sixty patients with stage II and III chronic periodontitis and bad breath. The patients were randomly divided into two groups (n=30). After conventional scaling and root planing, patients in group 1 underwent Er,Cr:YSGG laser (Waterlase; Biolase, San Clemente, CA, USA) irradiation of the internal surface of the pockets ( 1.5 W, 30 Hz, 20% A, 40% W) and the dorsum of the tongue (1 W, 30 Hz, 20%A, 40% W) immediately after SRP and on the third and seventh days. Group 2 patients were asked to use Halita mouthwash twice daily for one week. Baseline, 1 and 3-month post-treatment measurements of plaque index (PI), probing pocket depth (PPD), clinical attachment level (CAL), gingival index (GI), bleeding on probing (BOP) and organoleptic assessment of Halitosis severity were performed. Results: Significant improvement in all parameters was noted in both groups after 1 and 3 months, compared with baseline (P<0.05). The two groups had significant reductions which occurred in PPD, CAL, and BOP levels and the organoleptic score in 1 and 3 months after the intervention (P<0.05). Conclusion: Er,Cr:YSGG laser irradiation and Halita mouthwash as adjuncts to non-surgical periodontal therapy are both effective in the treatment of oral malodor and improvement of periodontal parameters. DOI:10.34172/jlms.2021.26